The Role of Interpersonal Communication with Clients in Supporting Work Effectiveness at PT. Antavaya Tour & Travel - Aurellia, Dennisa Arofani (Journal of Indonesian Tourism and Policy Studies, 2025)
Humans are social creatures who cannot live without other people around us. Humans also need to communicate with each other in order to become a basic need to share information with each other. Communication is also used as a measure of the effectiveness of a job. Communication is also divided into several meanings, one of which is interpersonal communication. Interpersonal communication is also used in the document division at PT. Antavaya Tour & Travel to support work effectiveness. Generally, the document division of PT. Antavaya Tour & Travel acts as a provider and service provider for making travel documents. Therefore, this final assignment discusses the role of client interpersonal communication in the document division to support the effectiveness of the document division. The purpose of this research is to find out how the role of communication is carried out by employees and clients, to find out how the effectiveness of the document division works. This study uses a type of qualitative research with data collection techniques, namely observation, interviews, and literature studies. The sources of this research are managers and supervisors from PT. Antavaya Tour & Travel. The results of this study indicate that the document division plays an important role for the continuity of making travel documents. It is hoped that the results of this research can provide useful information for readers, especially for those who want to know the process of making travel documents.